ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI INFORMASI PELAPORAN KEUANGAN PEMERINTAH DAERAH - Djawang, Rizky Rivaldo Peku; Made, Anwar; Sari, Ati Retna (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2019)
This study aims to determine the effect of SAP Understanding, Use of Information Technology, Internal Oversight, HR, and Organizational Commitment to the Value of Financial Statements, both partially and simultaneously. This research was conducted in East Sumba Regency - East Nusa Tenggara Province using primary questionnaire data distributed to DPKAD / DPPKD staff of the City / Regency of East Sumba. The sample used amounted to 35 people consisting of employees who work or handle the accounting department. The data analysis technique used in this study is multiple linear regression analysis. The results showed that SAP Understanding, Use of Information Technology, Internal Oversight, Human Resources, and Organizational Commitment simultaneously influence the Financial Statement Information Value and partially SAP Understanding, Use of Information Technology, Human Resources has a positive and significant effect on financial performance, but Internal Control and Organizational Commitment do not affect the value of financial statement information in East Sumba district. Based on these results it can be concluded that the greater the SAP Understanding, Use of Information Technology, Human Resources will improve the quality of regional financial statement information, and vice versa if the Understanding of SAP, Use of Information Technology, Human Resources decreases the quality of regional financial statement information will also decrease